Type II photoinitiator substituted zinc phthalocyanine: Synthesis, photophysical and photopolymerization studies - Korkut, Sibel Eken; Temel, Gokhan; Balta, Demet Karaca; Arsu, Nergis; Sener, M. Kasim (ELSEVIER, 2013)
The novel 4-(9-oxo-9 H-thioxanthen-2yloxy) phthalonitrile (TX-Pht) and its peripherally tetra substituted zinc phthalocyanine complex (TX-ZnPc) have been prepared and characterized by spectroscopic and elemental analysis techniques. Photoinitiated polymerization of methyl methacrylate (MMA) with TX-ZnPc has been investigated in the presence and absence of a co-initiator. Fluorescence and phosphorescence measurements have been also performed to determine the photophysical properties. Low fluorescence quantum yield (Phi(F)=0.08) compared to the unsubstituted ZnPc has been found. This allows initiator to undergo intersystem crossing into the triplet state and the lowest triplet state possesses pi-pi* configuration. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Thioxanthone; Photopolymerization; Type II photoinitiator; Fluorescence; POLYMERIZATION; DERIVATIVES; COMPLEXES; Optics